Development of a general purpose motion control systems for robots and vehicles - Wang, Changbin (2019)
Robots are now playing significant roles in our daily life. The motion control is one of the key technologies in the robotic industry. However, the motion control systems used today are still not stable enough for moving robots and self-driving vehicles. In this report, the author aimed to developed a general-purposed motion control system for robots and vehicles based on polynomial trajectory generation and PID control algorithm. The author has found that the actual value would gradually reach the desired value using the motion control system, but the result is not as perfect as ideal value. This report will explore the theory of PID motion algorithm, usage of hardware, and how to develop the motion control system.